Effect of standoff distance on the partitioning of surface heat flux during subcooled jet impingement boiling - Sridhar, Abishek; Narayanaswamy, R.; Narayanan, V. (2012)
Heat transfer involving boiling of impinging jets are used for cooling components that dissipate very large heat fluxes, typically over 100 W/cm2 concentrated at discrete locations. Several industrial applications requiring cooling of discretely heated components such as in power electronics, synchrotron x-ray, fusion, and semiconductor laser systems have found beneficial use of boiling impinging jets, particularly due to the large heat transfer coefficients obtained in the stagnation region. The present paper aims to investigate the effect of standoff distance on the partitioning of the surface heat flux during subcooled and confined submerged jet impingement boiling, for different heater sizes. The RPI wall-boiling model is employed for the partitioning of surface heat flux into liquid phase convective, quenching and evaporative heat fluxes, and solved in conjunction with the governing equations for flow and heat transfer. It is found that the standoff distance influences the characteristics of boiling only in the partial nucleate boiling regime. Besides, the influence was only on the liquid phase convective component of the total heat flux, while the quenching and evaporative components remained unaffected. The total heat flux in the partial nucleate boiling regime was consistently larger for smaller standoff distances, irrespective of the heater size. The change in the surface averaged liquid phase convective heat flux with change in standoff distance was also found to be larger for relatively smaller heater sizes in the partial nucleate boiling regime.